ANALYSIS OF THE EFFECT OF CUTTING SPEED AND CURRENT ON SURFACE ROUGHNESS WITH CNC PLASMA CUTTING ON STEEL PLATES SS400 - Susilo, Gunawan Budi; Sasongko, Beni Tri; Wardhana, Prabuditya Bhisma Wisnu (Department of Mechanical Engineering Education, 2024)
Surface roughness characteristics are very important data in the machining process. This study aims to determine how much influence the cutting speed and current variation with air pressure of 1 MPa on surface roughness of SS 400 steel plate cutting using CNC plasma cutting on roughness. The independent variables of the research are variations in cutting speed and current. Testing the cutting speed of the material removal rate (MMR) using the method of reducing the mass of the workpiece and calculating the empirical formula, testing the surface roughness using the surface roughness tester TR 1200. The data are presented in the form of tables and graphs. The results of the material removal rate test for reducing the mass of the workpiece, the lowest value obtained in this study was 378 mm/min3 with a cutting current of 110 A and the highest was 1890 mm/min3 with a cutting current of 100 A, while at the melting point at a current of 90, 100, 110 Ampere get a value of 0.444, 0.494, 0.543 cm/min3.baSe The results of the roughness test, which should be that the higher the melting point value, the higher the roughness level, at 90 Ampere cutting currents get an average value of 12,502 Î¼m, 100 Ampere currents have an average value of 8.653 Î¼m and, 110 Ampere currents have an average value of 7.56 Î¼m . Cutting speed affects the cutting current, the results of calculations using the mass weighing method and using calculations, the results of testing the measurement of the roughness value are getting smaller.